Latent iron deficiency in non-anemic children under five years of age - Qurat ul Ain Riaz; Saima Ahsan; Tanveer Hussain Chaudhary; Abdul Hafeez Soomro; Muhammad Sabir Khan; Shanza Nazish (Journal of Rawalpindi Medical College)
Background: The most common nutritional deficiency in world is iron deficiency. The iron deficiency is the most common cause of anemia due to nutritional deficiency and is seen most commonly in children under five years of age.